2017
DOI: 10.1021/acs.inorgchem.7b00835
|View full text |Cite
|
Sign up to set email alerts
|

α-Amino Acid Derived Benzimidazole-Linked Rhodamines: A Case of Substitution Effect at the Amino Acid Site toward Spiro Ring Opening for Selective Sensing of Al3+ Ions

Abstract: α-Amino acid derived benzimidazole-linked rhodamines have been synthesized, and their metal ion sensing properties have been evaluated. Experimentally, l-valine- and l-phenylglycine-derived benzimidazole-based rhodamines 1 and 2 selectively recognize Al ion in aqueous CHCN (CHCN/HO 4/1 v/v, 10 mM tris HCl buffer, pH 7.0) over the other cations by exhibiting color and "turn-on" emission changes. In contrast, glycine-derived benzimidazole 3 remains silent in the recognition event and emphasizes the role of α-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…However, while adding DCP at neutral pH the probe shows its deep pink color even at pH 8 (Fig. S 13 ) 39 , 40 , which demonstrates the practical applicability of the chemosensor.…”
Section: Resultsmentioning
confidence: 91%
“…However, while adding DCP at neutral pH the probe shows its deep pink color even at pH 8 (Fig. S 13 ) 39 , 40 , which demonstrates the practical applicability of the chemosensor.…”
Section: Resultsmentioning
confidence: 91%
“…Specifically, such compounds have been studied as dark or light‐controlled chemosensors for metal ions and Al 3+ in particular . There is always a demand for reliable and facile sensors for salts and compounds of Al …”
Section: Introductionmentioning
confidence: 99%
“…Then several aliquots of 50 µM in Benchmark buffer were prepared from this and stored at -20 °C for future use. Before the experiment, one aliquot was taken and heated at 95 °C for 5 min followed by chilled in Cell permeability and cell imaging by fluorescence microscope: The penetrations of C-992 in living and fixed cultured human cells were checked as per our earlier report [24]. In brief, human lung cancer A549 cells were grown on cover slips placed inside the Petri plate for 24 h. Then one set of the cover slip containing the adherent living cells was treated with 20 nM C-992 for 30 min in dark (without fixation).…”
Section: Methodsmentioning
confidence: 99%
“…In our case, it takes the same conformation as evident from the typical positive peak at 295 and 250 nm as shown in Fig 8. To observe the cellular uptake of this compound by the live-cell A549 under culture condition with and without using a fixative, we incubated the A549 cells in presence of a very low concentration (20 nM) of C-992 in PBS for 30 min at 37 °C as per our previous report [24,35,36]. Then the cell images were captured under bright field mode (data not Several reports showed that the G-quadruplex ligand can inhibit telomerase activity [35][36][37][38][39][40].…”
Section: G4-fid Assaymentioning
confidence: 99%